Vinyl-2-pyrrolidone derivatized guar gum based aqueous two-phase system - Kautharapu, Kumar; Pujari, Narahari S.; Golegaonkar, Sandeep B.; Ponrathnam, Surendra; Nene, Sanjay N.; Bhatnagar, D. (Separation and Purification Technology, 2009)
Aqueous two-phase systems (ATPs) are formed when certain combinations of two polymers or polymer and salt are added to water. Phase separation occurs at certain specific concentrations that have similar densities and low interfacial tensions. The present study involves synthesis and application of a novel derivatized guar in aqueous two-phase system. The derivation of guar gum was performed by grafting of 1-vinyl-2-pyrrolidone by a redox reaction in aqueous medium ceric ammonium nitrate (CAN) and potassium Peroxydisulfate(K2S2O8). The ratio of grafting efficiency (%GE) and ratio of grafting (%G) was 56% and 70.1% respectively. The grafted copolymers were characterized for percent yield and FTIR absorbance. A new aqueous two-phase extraction protocol was established using a mixture of derivatized guar and dextran. A phase diagram was constructed based on the phase separation exhibited by the system at 25 degrees C. The partition coefficient was determined for standard bovine serum albumin (BSA), lactate oxidase (LO) and phytase. The partitioning coefficients were 0.479, 1.981, and 2.586 respectively in the Dextran (2 mill ion)/V-GG/H2O system. The influence of an ionic salt sodium chloride (NaCl) was investigated on the partitioning of BSA. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Aqueous two phase; graft copolymers; Guar gum; Partition coefficient (K); Phase diagram; Vinyl pyrrolidone; viscosity

Discovery of rifampicin as a new anti-glycating compound by matrix-assisted laser desorption/ionization mass spectrometry-based insulin glycation assay - Golegaonkar, Sandeep B.; Bhonsle, Hemangi S.; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (European Journal of Mass Spectrometry, 2010)
An in vitro insulin glycation assay was developed for screening glycation inhibitors. The assay involves the use of matrix-assisted laser desorption/ionization time-of-flight mass spectrometry for monitoring the formation of glycated insulin. The assay is simple, rapid and amenable for high throughput screening. Using this assay we have discovered a strong anti-glycation activity for the anti-tuberculosis drug rifampicin. These results were compared with bovine serum albumin glucose fluorescence assay. In addition, the IC(50) of rifampicin was lower than that of aminoguanidine, a known anti-glycating agent, suggesting that rifampicin is a more potent glycation inhibitor.
Keywords: AGE; aminoguanidine; antibiotic; diabetic complication; drug repositioning; IC(50)

Low plasma albumin levels are associated with increased plasma protein glycation and HbA1c in diabetes - Bhonsle, Hemangi S.; Korwar, Arvind M.; Kote, Sachin S.; Golegaonkar, Sandeep B.; Chougale, Ashok D.; Shaik, Mahemud L.; Dhande, Nitin L.; Giri, Ashok P.; Shelgikar, Kishore M.; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (Journal of Proteome Research, 2012)
Albumin is one of the most abundant plasma proteins and is heavily glycated in diabetes. In this study, we have addressed whether variation in the albumin levels influence glycation of plasma proteins and HbA1c. The study was performed in three systems: (1) streptozotocin (STZ)-induced diabetic mice plasma, (2) diabetic clinical plasma, and (3) in vitro glycated plasma. Diabetic mice and clinical plasma samples were categorized as diabetic high albumin plasma (DHAP) and diabetic low albumin plasma (DLAP) on the basis of their albumin levels. For the in vitro experiment, two albumin levels, high albumin plasma (HAP) and low albumin plasma (LAP), were created by differential depletion of plasma albumin. Protein glycation was studied by using a combination of two-dimensional electrophoresis (2DE), Western blotting, and LC-MSE. In both mice and clinical experiments, an increased plasma protein glycation was observed in DLAP than in DHAP. Additionally, plasma albumin levels were negatively correlated with HbA1c. The in vitro experiment with differential depletion of albumin mechanistically showed that the low albumin levels are associated with increased plasma protein glycation and that albumin competes for glycation with other plasma proteins.
Keywords: advanced glycation end products (AGEs); Albumin; glucose; post translational modification

Preparation of cross-linked enzyme aggregates of L-aminoacylase via co-aggregation with polyethyleneimine - Vaidya, Bhalchandra K.; Kuwar, Suyog S.; Golegaonkar, Sandeep B.; Nene, Sanjay N. (Journal of Molecular Catalysis B-Enzymatic, 2012)
L-Aminoacylase from Aspergillus melleus was co-aggregated with polyethyleneimine and subsequently cross-linked with glutaraldehyde to obtain aminoacylase-polyethyleneimine cross-linked enzyme aggregates (termed as AP-CLEA). Under the optimum conditions, AP-CLEA expressed 74.9% activity recovery and 81.2% aggregation yield. The said method of co-aggregation and cross-linking significantly improved the catalytic stability of L-aminoacylase with respect to temperature and storage. AP-CLEA were employed for enantioselective synthesis of three unnatural amino acids (namely: phenylglycine, homophenylalanine and 2-naphthylalanine) via chiral resolution of their ester-. amide- and N-acetyl derivatives. The enantioselectivity of AP-CLEA was the highest for hydrolysis of amino acid amides; was moderate for hydrolysis of N-acetyl amino acids and was the least for hydrolysis of amino acid esters. Furthermore, AP-CLEA were found to retain more than 92% of the initial activity after five consecutive batches of (RS)-homophenylalanine hydrolysis suggesting an adequate operational stability of the biocatalyst. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: chiral resolution; Cross-linked enzyme aggregates; L-Aminoacylase; Polyethyleneimine; Unnatural amino acids

Proteome wide reduction in AGE modification in streptozotocin induced diabetic mice by hydralazine mediated transglycation - Kesavan, Suresh K.; Bhat, Shweta; Golegaonkar, Sandeep B.; Jagadeeshaprasad, Mashanipalya G.; Deshmukh, Arati B.; Patil, Harshal S.; Bhosale, Santosh D.; Shaikh, Mahemud L.; Thulasiram, Hirekodathakallu V.; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (Scientific Reports, 2013)
The non-enzymatic reaction between glucose and protein can be chemically reversed by transglycation. Here we report the transglycation activity of hydralazine using a newly developed MALDI-TOF-MS based assay. Hydralazine mediated transglycation of HbA1c, plasma proteins and kidney proteins was demonstrated in streptozotocin (STZ) induced diabetic mice, as evidenced by decrease in protein glycation, as well as presence of hydralazine-glucose conjugate in urine of diabetic mice treated with hydralazine. Hydralazine down regulated the expression of Receptor for Advanced Glycation End products (RAGE), NADPH oxidase (NOX), and super oxide dismutase (SOD). These findings will provide a new dimension for developing intervention strategies for the treatment of glycation associated diseases such as diabetes complications, atherosclerosis, and aging.